Conceptual Analysis of Problem-Based Learning Model in Improving Students Critical Thinking Skill - Nugraha, Markus Asta Patma; Sinolungan, Jehosua S.V.; Nur, Rezeki; Nuridah, Siti; Nofirman, Nofirman; Cahyono, Didik (Journal of Education Research, 2023)
The purpose of this research was to conceptually analyze the problem-based learning model in improving students' critical thinking skill. The research method used in this research was descriptive qualitative. The type of research was library research. Data collection techniques by collecting and analyzing documents descriptively, both written, image and electronic documents. The research results obtained were then presented descriptively in accordance with the research problems and objectives. The results of this research showed that the conceptual analysis of the problem-based learning model in improving students' critical thinking skill, namely Problem-based learning is a learning model that uses problems as a starting point for learning. In other words, problem-based learning is a problem-centered learning activity, Problem-based learning is a learning model that involves students to solve a problem through the stages of the scientific method so that students can learn knowledge related to the problem and at the same time have the skills to solve problems,  a learning model that uses real-world problems. This learning model aims to encourage students to learn through various real problems in everyday life that are related to the knowledge they have or will learn;, Problem-based learning model is a learning model that involves dominant student activities, the teacher acts as a facilitator.